Effect of geological heterogeneities on reservoir storage capacity and migration of CO2 plume in a deep saline fractured carbonate aquifer. (June 2021) - Sohal, M. Adeel; Le Gallo, Yann; Audigane, Pascal; de Dios, J. Carlos; Rigby, Sean P.
Highlights: Matrix permeability heterogeneity decreased the CO2 reservoir storage capacity of a deep saline fractured limestone aquifer. CO2 is stored in the topmost layer of the homogeneous limestone compared to a heterogeneous fractured limestone. The saturation of gas from top to bottom was higher in the heterogeneous fractured limestone case. The heterogeneity based on porosity variation significantly increased the reservoir storage capacity of the fractured limestone. Abstract: In a reservoir characterization study of the Hontomín deep saline aquifer, the impact of geological heterogeneities on reservoir storage capacity and the migration of the CO2 plume is explored. This work presents, for the first time, very long-term (up to 200 years) simulations of CO2 injection into the naturally fractured Sopeña Formation, of the lower Jurassic age, at Hontomín. CO2 injection was simulated as a dual permeability case with Eclipse compositional software. The matrix permeability of the carbonate reservoir is quite low (0.5 mD) and thus fluid flow through the fractures dominates. The reservoir is dissected by eight normal faults which limited its south-east extension and divided it into several segments. The effect of geological heterogeneities was tested through scenario-based modeling and variation of parameters characterizing heterogeneity within realistic limits based on other similar formations. This modeling approach worked well in Hontomín where the database is completely scarce. The plume migration, the reservoir storage capacity, and pressure, were each influenced in diverse ways by incorporating particular types of heterogeneities. The effect of matrix heterogeneities on reservoir storage capacity was substantial (by factors up to ∼2.8×), compared to the plume migration. As the reservoir matrix permeability heterogeneity increased, the reservoir storage capacity markedly decreased, whilst an increase in porosity heterogeneity significantly increased it. The vertical gas migration in the homogeneous base case was relatively larger compared to the heterogeneous cases, and gas accumulated underneath the caprock via hydrodynamic trapping. It was also observed that, in heterogeneous cases, gas saturation in rock layers from top to bottom was relatively high compared to the base case, for which most of the gas was stored in the topmost layer. In contrast, the impact on storage capacity and plume movement of matrix vertical to horizontal permeability ratio in the fractured carbonate reservoir was small. The impact of the transmissibility of faults on reservoir pressure was only observed when the CO2 plume reached their vicinity.